A Multi‐Transition Approach to Evaluating Peacekeeping Effectiveness. (28th July 2020) - Kim, Wukki; Sandler, Todd; Shimizu, Hirofumi
SUMMARY: Past studies of the effectiveness of peacekeeping operations (PKOs) mainly focus on the preservation of peace. If the transitions from peace to conflict or from conflict to peace are correlated based on grievances or war weariness, then a multi‐transition survival analysis provides more efficient estimates and may limit bias. Our main analysis for 133 country‐based conflicts during 1990–2016 shows that estimates of the two transitions display a significant negative covariance, consistent with grievances and the need for a multi‐transition approach. As a robustness check, we match UN PKOs with the absence of UN PKOs to address nonrandom assignments of PKOs. For the matched and unmatched estimates, we find that UN peace enforcement missions induce a transition from conflict to peace, while UN observation, traditional peacekeeping, and peacebuilding missions limit a transition from peace to conflict. We also show that UN troops, rather than UN police, are more effective in transitioning from conflict to peace and in maintaining peace after conflict. Further robustness runs for alternative subsamples (e.g., just civil wars) support the main results. Our findings indicate the appropriate UN PKO mission type and personnel mix to deploy depending on the conflict's current state.